Sub microsecond analysis of negative cloud-to-ground lightning flashes - Abdul Rahman, Ahmad Idil; Baharudin, Zikri Abadi; Bahari, Muhammad Akmal; Zulkefle, Ahmad Aizan; Zainon, Maslan; Mat Hanafiah, Mohd Ariff (Institute Of Advanced Engineering And Science (IAES), 2018)
This paper expounds a software development for the identification of lightning discharged in cloud-to-ground flashes.The study was to reduce a misleading detection of the electric field radiation of lightning discharged profile by considering the important parameters of sub microseconds structure of lightning`s first return stroke.The software built in MATLAB.The software development considered the important parameters of the first return strokes such as peak value,zero crossing, rising time and fast transition time.This study used a modelling technique for training and patterning 19 return strokes from electric radiation field generated by the negative cloud-ground lightning flashes recorded in Universiti Teknikal Malaysia Melaka.19 return strokes data were recorded by using Lecoy HDO4024 with 5 MS/s.The results showed the software recognized the lightning parameters such as peak value,zero crossing,rising time and fast transition time.In conclusion,the software had the potential to decreases the misleading detection of the electric field radiation generated by negative cloud-to-ground lightning flashes.